1977
DOI: 10.1246/bcsj.50.1920
|View full text |Cite
|
Sign up to set email alerts
|

On the Phase Transition of Ammonium Hexafluoroferrate(III)

Abstract: The heat capacities of (NH4)3[FeF6] crystal have been measured from 15 to 350 K with an adiabatic calorimeter. A heat capacity anomaly was observed at 267.02±0.05 K. The enthalpy and entropy changes of the transition are 6490±500 J mol−1 and 24.8±1.9 J K−1 mol−1, respectively. This value of entropy was discussed in terms of a model involving orientational disorder of the ammonium as well as hexafluoroferrate(III) ions. Based on the assumption of the average fcc symmetry of the crystal and internal rigidity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…Ammonium cryolite, (NH4)3A1F6, shows two phase transitions at 193 and 220.8 K. Calorimetric measurements of ASt .... (23.05 JK-a tool-1) is in agreement with R In 16 indicating orientational disorder of the [A1F6] octahedra and (NH,~) ions (Moriya et al 1979). The ASt .... for the single phase transition in (NH4)3FeF6 at 267 K is also equal to R In 16 (Moriya et al 1977). A 57Fe M6ssbauer resonance study of the phase transition in this compound indicates a zero nuclear quadrupole coupling constant in the cubic phase (Morup and Thrane 1972).…”
Section: Transition Mechanisms In Other Mixed Fluoride Perovskites Anmentioning
confidence: 82%
See 2 more Smart Citations
“…Ammonium cryolite, (NH4)3A1F6, shows two phase transitions at 193 and 220.8 K. Calorimetric measurements of ASt .... (23.05 JK-a tool-1) is in agreement with R In 16 indicating orientational disorder of the [A1F6] octahedra and (NH,~) ions (Moriya et al 1979). The ASt .... for the single phase transition in (NH4)3FeF6 at 267 K is also equal to R In 16 (Moriya et al 1977). A 57Fe M6ssbauer resonance study of the phase transition in this compound indicates a zero nuclear quadrupole coupling constant in the cubic phase (Morup and Thrane 1972).…”
Section: Transition Mechanisms In Other Mixed Fluoride Perovskites Anmentioning
confidence: 82%
“…A 57Fe M6ssbauer resonance study of the phase transition in this compound indicates a zero nuclear quadrupole coupling constant in the cubic phase (Morup and Thrane 1972). Although the iron environment is cubic on the average, the disorder model (Moriya et al 1977) implies that it deviates from the cubic symmetry when observed for a short duration of time. The average octahedral symmetry in the cubic phase is achieved by random jumping of [FeF6] groups over eight configurations.…”
Section: Transition Mechanisms In Other Mixed Fluoride Perovskites Anmentioning
confidence: 87%
See 1 more Smart Citation
“…22). " The (NH,')" ions, too, would then be of symmetry C I , and four v, quartets and four V4bc octets would be expected, ''The T,, obtained from C,, measurements (24,25) and listed in Table 1 do not always agree with the estimates from X-ray powder diffraction, dta, esr, ir, and other measurements (5,26,27,33,34). A pronounced tendency to undercooling has been reported for the intermediate phase of 59 (24), and similar hysteresis phenomena known to exist in other complex fluorides (e.g.…”
Section: Fig 1 Schematic Representation Of the Hydrogen Bonding Inmentioning
confidence: 87%
“…"Low-temperature phase is derived from the Fn13m phase by triclinic distortion (5,13). 'A-point, AS,,/R = 3.0 (25).…”
mentioning
confidence: 99%